Youth Studies and Generations: Values, Practices and Discourses on Generations - Ferreira, Vitor Sérgio (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
There is currently much discourse about generations in the public sphere. A sequence of letters conflates generations and age cohorts born in the last few decades (generation "X", "Y" or "Z") as well as multiple categories are used to describe today's young people as a generation that is distinct from its predecessors. Despite the popularity of generational labels in media, politics, or even academia, the use of generation as a conceptual tool in youth studies has been controversial. This Special Issue allows readers to better understand the key issues regarding the use of generation as a theoretical concept and/or as a social category in the field of youth studies, shedding light on the controversies, trends, and cautions that go through it.